Biostratigraphical investigation of middle-early Miocene sediments from a section of AK-1 well, onshore Niger Delta: Insights from calcareous nanofossils (Fountain Journal of Natural and Applied Sciences, 2023)
Biostratigraphic analysis was carried out on KA-1 well, onshore Niger Delta Basin of Nigeria. A total of forty (40) ditch cutting samples were collected from the studied section at 30 feet depth intervals with the studied section ranging from 7590-4800feet. The objectives of this study are to determine the age and biozonation of the studied section. Using simple smear slide method, the samples were processed and analyzed for nannofossils using a reflected binocular microscope. Calcareous nannofossil assemblages from the well are of low diversity and abundance. Some depths yielded almost monospecific assemblages while some have no records of calcareous nannofossils. Species include Helicospharea ampliaperta, Sphenolithus heteromorphus, Cyclicargolithus floridanus, Helicospharea scissura and Discoaster deflander. These belong to the NN4 zone of middle to early Miocene age.Keywords: Biozonation, Calcareous nannofossils, Helicospharea ampliaperta, Oligotrophic, Niger Delta.
Keywords: Biozonation, Helicospharea ampliaperta, Calcareous nannofossils, Oligotrophic, Niger Delta.